The LPGAs battle for success : a discussion of sponsorship in relation to the organizational decisions of the LPGA - Studin, Rebecca; Mahoney, Tara Q.; Dodds, Mark (London : SAGE Publications Ltd, 2017)
This case study centers on sponsorship, marketing, and policy decisions in relation to the Ladies Professional Golf Association (LPGA)s recent struggles as an organization. Students receive a brief history of golf as well as a description of recent issues faced by the LPGA, including lack of an American fan base, questionable policy decisions and the organizations shortage of marketable, celebrity superstars. With this background, students are asked to discuss several recommendations to improve on one or more of these previous issues.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Ladies Professional Golf Association; Athletic clubs -- Marketing -- Case studies; Golf -- Case studies